Nursing with a message : public health demonstration projects in New York City - D'Antonio, Patricia, 1955- (Critical issues in health and medicine., 2017)
"Focuses on demonstration projects and health centers in New York City in the interwar years. One of the clear strengths of the movement was its acknowledged dependence on nurses - especially public health nurses - to visit family after family, neighborhood after neighborhood, school after school, and church after church to encourage the adoption of healthier lifestyles, preventive physical exams, well child care, and routine dental care. Their work established the norms of primary care now practiced in today's primary care centers. But their work was highly labor intensive and depended on the breakdown of disciplinary boundaries among nurses, physicians, and social workers that had been painstakingly created in the decades before the War. This almost happened - until the ravages of the Great Depression of the 1930s forced retrenchments that stifled continued innovation. Nursing with a Message explores the day-to-day processes involved in the coming together and moving apart of different organizations, disciplinary interests, knowledge domains, and spheres of public and private responsibilities involved in caring for those in need at the point of delivery of service. More specifically, it uses the public health nurses involved in New York City health demonstration projects as a case study of disciplinary tensions inherent in projects with multiple constituents and invested in multiple, and sometimes contradictory outcomes. It shows how one central public health discipline searched for better ways to care for the people it served even as it attended to its own advancement, place, and power in a very complicated space of ideas, practice, action, and actors. But the prerogatives of gender, class, race, and disciplinary interests shaped their implementation"--